Social enterprises as a tool for supporting housing supply in compliance with the Agenda 2030 - Sika, Peter; Vidová, Jarmila; Kordoš, Marcel (Business: Theory and Practice, 2025)
There is a space at the interface between the public and state sectors and the private profitable, market sector for the operation of the social economy. The social economy is a socially beneficial area in solving social problems in many countries of the European Union and is still consolidating its position in terms of the Agenda 2030. The paper presents a framework of new and unexplored issues, where the novelty a current overview of the role of social enterprises in providing housing support for low-income groups in regions of the Slovak Republic with elevated unemployment rates, in alignment with the objectives set forth in Agenda 2030. We also focus on the potential of social enterprises in solving the issue of housing for people with insufficient income in marginalized communities, as this area has received little attention in Slovakia. As part of the empirical part, we conducted an analysis of the development of social enterprises and their establishment in the regions. Since a quarter of the social enterprises are located in the least developed regions, where unemployment is significantly worse than the Slovak average, we examined by correlation whether there is a dependence between the number of available job seekers of working age in % of the working age population in individual regions of the Slovak Republic and the number of social enterprises established in the regions of the Slovak Republic. From empirical research, we can identify that social housing enterprises are an important tool that helps solve the issue of housing for people who do not have sufficient income to secure it however, the absence of effective financial support results in their uniform composition.